2009
DOI: 10.1523/jneurosci.4315-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin 1 Receptors Regulate Morphine-Induced Endocytosis and Desensitization of μ-Opioid Receptors in CNS Neurons

Abstract: -Opioid receptors (MORs) are G-protein-coupled receptors (GPCRs) that mediate the physiological effects of endogenous opioid neuropeptides and opiate drugs such as morphine. MORs are coexpressed with neurokinin 1 receptors (NK1Rs) in several regions of the CNS that control opioid dependence and reward. NK1R activation affects opioid reward specifically, however, and the cellular basis for this specificity is unknown. We found that ligand-induced activation of NK1Rs produces a cell-autonomous and nonreciprocal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 51 publications
1
49
0
Order By: Relevance
“…As DOR and MOR interact (in the cell membrane) and DOR modulates the function of MOR (Gomes et al 2004), TACRs (via MOR or indirectly via DOR) would modulate the activity of the opioid receptors. In this study, the knockdown of ZfDOR2 and ZfMOR regulated the expression of tacr1a and tacr1b respectively, indicating that tachykinin and the opioid systems are closely interrelated in zebrafish, as has been described in mammals (Minami et al 1995, Pfeiffer et al 2003, Guan et al 2005, Yu et al 2009). As the set of MOs of opioid receptors was effective, as previously demonstrated by Sanchez-Simon et al (2010), and replicated in our study, we are convinced that the changes on the expression of the TACRs are a consequence of the downregulation of the opioid receptors.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…As DOR and MOR interact (in the cell membrane) and DOR modulates the function of MOR (Gomes et al 2004), TACRs (via MOR or indirectly via DOR) would modulate the activity of the opioid receptors. In this study, the knockdown of ZfDOR2 and ZfMOR regulated the expression of tacr1a and tacr1b respectively, indicating that tachykinin and the opioid systems are closely interrelated in zebrafish, as has been described in mammals (Minami et al 1995, Pfeiffer et al 2003, Guan et al 2005, Yu et al 2009). As the set of MOs of opioid receptors was effective, as previously demonstrated by Sanchez-Simon et al (2010), and replicated in our study, we are convinced that the changes on the expression of the TACRs are a consequence of the downregulation of the opioid receptors.…”
Section: Discussionsupporting
confidence: 67%
“…expression (of Tacr1a and Tacr1b) in whole-mount zebrafish embryos in one stage of embryonic development (48 hpf) while the other studies were done in adult rats and mice. Also, several studies have described that TACR1/MOR functionally interact and mediate the regulation of MOR-TACR1 trafficking, where the activation of TACR1 by SP can induce or inhibit the endocytosis of MOR (Pfeiffer et al 2003, Yu et al 2009). Our results show that downregulation of ZfMOR increases the expression of tacr1b, suggesting that MOR could be positively regulating TACR1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors demonstrated, firstly in HEK293 cells, that the chimeric mu-delta receptor construct previously described predominantly in recycling endocytic vesicles [53]. Another recent report has described the regulation of mu receptor endocytosis and desensitisation by NK1 neurokinin receptors [54].…”
Section: Regulators Of G-protein Signalling (Rgs) Is Other Family Of mentioning
confidence: 90%
“…In addition, this heterologous pairing also resulted in a functionally significant attenuation of morphine-induced desensitisation of mu receptor signalling via adenylyl cyclases. Studies involving over-expression of β-arrestin 2-GFP and a neurokinin 1 receptor mutant unable to interact with β-arrestin2 indicated that the negative modulation of mu receptor endocytosis by 21 the neurokinin 1 receptor might be achieved by sequestering arrestins in endosomes and hence limited their availability to interact with the mu receptor [54].…”
Section: Regulators Of G-protein Signalling (Rgs) Is Other Family Of mentioning
confidence: 99%